An effective recombinant protein expression and purification system in Saccharomyces cerevisiae - Xie, Ying (2020)
The expression and purification of recombinant proteins using bacterial vectors is a mature and preferred system to obtain folded and stable proteins. However, functional post‐translational protein modifications, such as glycosylation or phosphorylation, can only be achieved using eukaryotic expression systems. In addition, insolubility is another challenge when using proteins expressed in Escherichia coli, such as certain intrinsically disordered proteins, which are more prone to aggregation than folded proteins. Eukaryotic protein expression systems, including human cells, baculovirus/insect cells, and yeast, have become indispensable for the production of functional eukaryotic proteins. This article describes a detailed protocol for performing cytosolic protein expression, protein purification, and protein characterization using the budding yeast Saccharomyces cerevisiae. The introduced protein expression and purification system in yeast are advantageous due to the low cost, high yield, high protein solubility, and minimal expertise required.